Assessment of the PNE (2014-2024): Affirmative action policies in higher education - Carreira, Denise (2024)
Based on research results coordinated by the authors, this article examines the challenges presented by the Plano Nacional de Educação [National Education Plan] (PNE) (2014-2024) and offers recommendations for the forthcoming PNE regarding affirmative actions in higher education. Despite numerous advancements, particularly following the implementation of the Quota Law (Law n. 12,711, 2012), three major challenges persist: the inadequate institutionalization of these policies within universities, which are still viewed as the responsibility of entities related to student assistance and/or ethnic-racial equality; the significant reduction in funding for higher education resulting from severe fiscal austerity measures that have hampered the conditions necessary for student retention in recent years; and the insufficient emphasis on affirmative actions within the Sistema Nacional de Avaliação da Educação Superior [National Higher Education Evaluation System].